Performance analysis of communication model on position based routing protocol : review analysis - Himawan, Hidayatulah; Hassan, Aslinda; Bahaman, Nazrul Azhar (Informatica, 2022)
Research on the Vanet system always has its own challenges and obstacles. The communication system between nodes is certainly the main problem that is always faced. The communication model and concept in the routing protocol process is a very decisive choice to get good communication quality. Four categories in vanet system topology, namely position based routing protocols, broadcast based routing protocols, cluster based routing protocols and multicast/geocast routing protocols, have fundamental differences, especially in the concept of sending data and information between nodes. For this reason, in this study, the selection of standardization and integration of data delivery between nodes is of particular concern and is certainly an interesting thing to study more deeply. The ability to send data properly in busy and fast traffic conditions has its own challenges. For this, there are many variables that must be considered, so that communication between nodes will be better.